Southampton Mealtime Assistance Study: design and methods. - Roberts, H; Pilgrim, A; Elia, M; Jackson, A; Cooper, C; Sayer, A; Robinson, S (BioMed Central, 2013)
BACKGROUND: Malnutrition is common in older people in hospital and is associated with adverse clinical outcomes including increased mortality, morbidity and length of stay. This has raised concerns about the nutrition and diet of hospital in-patients. A number of factors may contribute to low dietary intakes in hospital, including acute illness and cognitive impairment among in-patients. The extent to which other factors influence intake such as a lack of help at mealtimes, for patients who require assistance with eating, is uncertain. This study aims to evaluate the effectiveness of using trained volunteer mealtime assistants to help patients on an acute medical ward for older people at mealtimes. METHODS/DESIGN: The study design is quasi-experimental with a before (year one) and after (year two) comparison of patients on the intervention ward and parallel comparison with patients on a control ward in the same department. The intervention in the second year was the provision of trained volunteer mealtime assistance to patients in the intervention ward. There were three components of data collection that were repeated in both years on both wards. The first (primary) outcome was patients' dietary intake, collected as individual patient records and as ward-level balance data over 24 hour periods. The second was clinical outcome data assessed on admission and discharge from both wards, and 6 and 12 months after discharge. Finally qualitative data on the views and experience of patients, carers, staff and volunteers was collected through interviews and focus groups in both years to allow a mixed-method evaluation of the intervention. DISCUSSION: The study will describe the effect of provision of trained volunteer mealtime assistants on the dietary intake of older medical in-patients. The association between dietary intake and clinical outcomes including malnutrition risk, body composition, grip strength, length of hospital stay and mortality will also be determined. An important component of the study is the use of qualitative approaches to determine the views of patients, relatives, staff and volunteers on nutrition in hospital and the impact of mealtime assistance. TRIAL REGISTRATION: Trial registered with ClinicalTrials.gov NCTO1647204.